The compatibility of osmotic and vapour equilibrium techniques in establishing soil-water characteristics curve : a case study for bentonite - Nurhidayah, Mahazam (2017)
The use of bentonite has been widely applied in geoenvironmental engineering applications for treatment, remediation and waste control. Bentonites in various forms are commonly used for containment, buffer material in landfills and high level nuclear waste (HL W) disposal repositories. Characterisation of locally available bentonite is crucial for development of HL W repository in Malaysia. Several researchers have showed that soil structure, initial water content, mineralogy, density, stress history, confining stress and compaction have considerable influence on the soil-water characteristic curves (SWCCs). SWCCs are frequently being established in the laboratory for estimation of unsaturated soil behaviour functions. In characterizing and establishing suction-water content SWCCs, osmotic and vapour equilibrium techniques (VET) are widely used. Problem associated with an intrusion of polyethylene glycol (PEG) into soil specimen in osmotic tests at high applied suction that may cause the degradation of the semi-permeable membrane, thus making it sensitive to microbial attack and affecting the SWCCs established. In this study, the physical, chemical, mineralogical and microbiological properties of Andrassy bentonite were determined following the standard procedures. Meanwhile, there were two disinfections methods were used to eliminate microbes by using antimicrobial and Ultra-Violet Germicidal Irradiation (UVGI) Exposure. Besides that, the suction-water content SWCCs during drying and wetting were established using osmotic and vapour equilibrium techniques at applied suctions of 0.15 to 262.75 MPa. In order to minimise the effect of PEG intrusion in osmotic test, an attempt was made to evaluate the effectiveness of antimicrobials and UVGI exposure in removal of cellulose degrading soil microbes. Three types of antimicrobial were considered namely penicillin, iodine and eucalyptus oil. Minimum Inhibitory Concentration (MIC) tests were conducted on all three antimicrobials in PEG solutions with varying concentrations of 10, 20, 40, 80, 160 and 200 ,ul, whereas UVGI exposure was carried out at different exposure time of 5, 10, 15, 30, 60 minutes. Based on the results, Andrassy bentonite can be classified as clay with high plasticity due to high cation exchange capacity (CEC) and high surface charge characteristics. The bentonite predominantly consists of montmorillonite mineral (63.2%). Chemical analysis indicated that the bentonite is sodium based monovalent bentonite. A total number of eight microbes were determined from the soil specimen. Water contents for the bentonite obtained from osmotic tests were found to be lower than water contents obtained from vapour equilibrium tests at applied suction of 3.65 to 9.96 MPa. Intrusion of PEG was observed. Paecilomyces lilacinus and Trichoderma atroviridae may be responsible for the degradation of cellulose acetate membrane used in the osmotic tests. Based on the findings of this study, UVGI exposure of 10 minutes was found to be the most effective method in eliminating all microbes and minimised the effect of PEG intrusion. A more precise suction-water content SWCC was established for the bentonite after UVGI exposure and thus improved the compatibility of both techniques at higher applied suctions.